Cascadedness in Chinese written word production - Qu, Qingqing; Damian, Markus F. (Frontiers in Psychology, 2015)
In written word production, is activation transmitted from lexical-semantic selection to orthographic encoding in a serial or cascaded fashion? Very few previous studies have addressed this issue, and the existing evidence comes from languages with alphabetic orthographic systems. We report a study in which Chinese participants were presented with coloured line drawings of objects and were instructed to write the name of the colour while attempting to ignore the object. Significant priming was found when on a trial, the written response shared an orthographic radical with the written name of the object. This finding constitutes clear evidence that task-irrelevant lexical codes activate their corresponding orthographic representation, and hence suggests that activation flows in a cascaded fashion within the written production system. Additionally, the results speak to how the time interval between processing of target and distractor dimensions affects and modulates the emergence of orthographic facilitation effects.